Chemomechanical versus drilling methods for caries removal: an in vitro study - Kemporn KITSAHAWONG; Ana Lucia SEMINARIO; Patimaporn PUNGCHANCHAIKUL; Anoma RATTANACHAROENTHUM; Waranuch PITIPHAT (Sociedade Brasileira de Pesquisa Odontológica, 2015)
The purpose of this study was to compare the performance of chemomechanical caries removal (CMCR) with that of conventional drilling for efficacy of caries removal, time spent, morphological changes and microhardness of surface dentin, and microleakage of subsequent restorations. Forty-six carious deciduous molars were randomly divided into two groups: one each for caries removal by (1) CMCR and by (2) drilling. The completeness of caries removal was evaluated by visual and tactile criteria and a caries detector device. Twenty teeth in each group were restored with glass ionomer (GI) and subjected to thermocycling before undergoing microleakage and microhardness tests. In each group, three restored teeth were used for polarized light microscopic analysis, and three unrestored teeth for scanning electron microscopy (SEM). There was no significant difference in the completeness of caries removal between groups. However, time spent for caries removal by CMCR was significantly longer than that required for drilling. Restorations in the CMCR group had significantly more microleakage than those in the drilling group. Dentin hardness of the cavity floor after CMCR was also significantly lower. Microscopic analyses showed roughened and irregular dentin surfaces in the CMCR group, unlike the smooth surfaces observed in the drilling group. In conclusion, CMCR was as efficacious as drilling in term of completeness of caries removal, but required longer excavation times and resulted in lower microhardness of residual dentin as well as more microleakage after restorations with GI. Further laboratory and clinical evaluations on the efficiency and performance of CMCR for the durability of subsequent restorations are required.